2022
DOI: 10.1177/10398562221142453
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence to second-generation antipsychotic long-acting injectable medications for schizophrenia: A comparative study in the Australian context

Abstract: Objective To examine patient characteristics, persistence and adherence to treatment associated with use of second-generation antipsychotic long-acting injectable (SGA LAI) medications in the Australian real-world setting. Method Five SGA LAIs were compared using a retrospective 10% sample of prescriptions in Australian Pharmaceutical Benefits Scheme (PBS) data: paliperidone palmitate 1-monthly (PP1M), paliperidone palmitate 3-monthly (PP3M), aripiprazole monohydrate (ARI), risperidone (RLAI) and olanzapine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this regard, a real-world study from Australia comparing treatment continuation between newer LAIs in a cohort of over 700 patients 42 showed that patients treated with PP3M had higher compliance rates (78%) and a longer period of continuous use (36 months) compared to PP1M (46%, 11 months), risperidone-LAI (33%, 4 months), olanzapine-LAI (35%, 8 months) and aripiprazole-LAI (51%, 18 months). 42 Moreover, a recent population-based study, including 2275 patients with schizophrenia, demonstrated that time to medication switch was substantially longer for patients on PP3M, with over 90% continuing treatment at 12 months, whereas those receiving PP1M, aripiprazole 1-monthly (AM) or oral antipsychotics were three times more likely to change treatment over the same period of time. 43 Patients with schizophrenia from an US Medicaid database who transitioned to PP3M were 2.4 times more likely to be adherent and 4.6 times more likely to be persistent than patients on PP1M during the 12-month follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a real-world study from Australia comparing treatment continuation between newer LAIs in a cohort of over 700 patients 42 showed that patients treated with PP3M had higher compliance rates (78%) and a longer period of continuous use (36 months) compared to PP1M (46%, 11 months), risperidone-LAI (33%, 4 months), olanzapine-LAI (35%, 8 months) and aripiprazole-LAI (51%, 18 months). 42 Moreover, a recent population-based study, including 2275 patients with schizophrenia, demonstrated that time to medication switch was substantially longer for patients on PP3M, with over 90% continuing treatment at 12 months, whereas those receiving PP1M, aripiprazole 1-monthly (AM) or oral antipsychotics were three times more likely to change treatment over the same period of time. 43 Patients with schizophrenia from an US Medicaid database who transitioned to PP3M were 2.4 times more likely to be adherent and 4.6 times more likely to be persistent than patients on PP1M during the 12-month follow-up period.…”
Section: Resultsmentioning
confidence: 99%